"Strengthening Performance Accountability in Honduras" : Institutional Governance Review : Background Chapters - World Bank (World Bank, 2012)
Having achieved fundamental milestones in terms of representative democracy and institutional modernization, Honduras continues to face important challenges in its bid to provide public services with coverage and quality commensurate with the resources available to the country. Honduras has come a long way in its democratic development, with seven free elections held since 1981 and the military subordinated to civilian control. Since the 1980s, the country has undertaken key public sector management reforms and has all of the formal components of a modern democracy. However, its average rate of economic growth and its degree of progress in reducing poverty over the past two decades have been low relative to most other Latin American countries, at this growth rate, Honduras will reach the current income per capita of El Salvador ($2,530) in 2050. Efficiency of public spending continues to be very low compared to regional standards, and the capacity of the public administration insufficient for ensuring the minimum goal of universal coverage of basic services. A general conclusion, highlighted throughout the study, is the need to strengthen the country's accountability framework and in particular, the accountability of policymakers towards citizens and tax payers, and to focus the policy discussion on performance.